2018
DOI: 10.3892/ol.2018.9436
|View full text |Cite
|
Sign up to set email alerts
|

miR-145-5p inhibits the proliferation and migration of bladder cancer cells by targeting TAGLN2

Abstract: MicroRNA-145-5p (miR-145-5p) is found to be involved in tumor development and progression. However, there are few studies on the effects of miR-145-5p on bladder cancer (BC). The role of miR-145-5p in BC was predicted by analysis of cell proliferation and migration in this study. The miR-145-5p and transgelin-2 (TAGLN2) expressions were evaluated via reverse transcription-quantitative PCR (RT-qPCR) or western blot analysis. The MTT and Transwell assay assessed cell proliferation and migration. TAGLN2 targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 26 publications
2
83
1
Order By: Relevance
“…In addition, it should be noted that the role of TAGLN2 regulating cell migration and invasion by affecting the cytoskeleton may not specifically function in the process of embryo implantation. Researches showed that TAGLN2 was highly expressed in kinds of malignant tumors and it could promote the invasiveness and metastasis (38)(39)(40). Besides, we observed high expression level of TAGLN2 in the decidualized mice endometrium, so we speculated that TAGLN2 may also be involved in endometrium remodeling through similar mechanisms to better adapt to the embryo implantation.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, it should be noted that the role of TAGLN2 regulating cell migration and invasion by affecting the cytoskeleton may not specifically function in the process of embryo implantation. Researches showed that TAGLN2 was highly expressed in kinds of malignant tumors and it could promote the invasiveness and metastasis (38)(39)(40). Besides, we observed high expression level of TAGLN2 in the decidualized mice endometrium, so we speculated that TAGLN2 may also be involved in endometrium remodeling through similar mechanisms to better adapt to the embryo implantation.…”
Section: Discussionmentioning
confidence: 72%
“…TAGLN2 is considered as a smooth muscle cytoskeletal protein ( 53 ). It has been proposed to be associated with growth and migration in bladder cancer ( 54 , 55 ), esophageal squamous cell carcinoma ( 56 ), and gliomas ( 57 ). Moreover, it's up-regulation is associated with tumorigenesis and tumor progression ( 54 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed to be associated with growth and migration in bladder cancer ( 54 , 55 ), esophageal squamous cell carcinoma ( 56 ), and gliomas ( 57 ). Moreover, it's up-regulation is associated with tumorigenesis and tumor progression ( 54 , 58 ). Silence of TAGLN2 in gliomas cell lines significantly inhibited invasion and tumor growth ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-145-5p displays an essential malignancy-repressing impact on malignancy progression [26,27]. MiR-145-5p expression was repressed in several malignancies, such as non-smallcell lung cancer (NSCLC), ESCC, cervical cancer, and colorectal cancer, wherein it could repress malignancy generation [28][29][30]. Metadata proved that miR-145-5p is remarkably downregulated in NSCLC compared with that in normal tissues and could assist in a more accurate diagnosis in lung squamous cell carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%